The Great Transformation II: Human Rights Leapfrogging in the Era of Globalization - Howard-Hassmann, Rhoda (Conference Papers -- American Political Science Association, 2003)
Whether globalization will result in improvement or deterioration in protection of human rights is not a matter that can be observed in the short term. Globalization is, in effect, the second ‘great transformation’ (Polanyi) spreading capitalism over the entire world. In consequence, many of its short-term effects will be negative. Nevertheless, its medium and long-term effects may well be positive, as it impels social changes that will result in greater moves to democracy, economic redistribution, the rule of law, and promotion of civil and political rights. Capitalism is a necessary, though hardly sufficient condition for democracy: democracy is the best, though not the inevitable, political system to protect human rights. This does not mean that the non-Western world will follow the exact same path to protection of human rights that the Western world followed. The West had a singular advantage: it was not expected to protect human rights during its own era of economic expansion. Thus, the West was able to practice slavery, expel surplus populations, and colonize other parts of the world. Genocide and ethnic cleaning were permissible state activities. The non-Western world does not enjoy the advantage of human rights lawlessness. It does, however, enjoy other advantages occasioned by the presence of human rights. There is a global communications network and a global pro-human rights social movement. There is also the movement to global governance. Finally, and paradoxically, there is the global social movement against globalization, which forces some reflection upon its deleterious consequences. Thus, the non-Western world benefits from geographical and chronological human rights ‘leapfrogging’. This, along with the social changes that global capitalism and industrialism may impel, may mean that the medium and long-term consequences of globalization are positive for human rights.
Keywords: capitalism; democracy; globalization; human rights; human rights advocacy; social change

Institutions, Politics and Culture: a Polanyian Perspective on Economic Change - Harriss, John (International Review of Sociology, 2003)
Presents the perspective of philosopher Karl Polanyi on economic change. Works of Polanyi on the topic; Analysis of pre-modern economies by Polanyi. According to Jeffrey Nugent, institutions make social life fairly predictable by restricting some actions and providing incentives for other actions. The article discusses Polanyi's book "The Great Transformation," the self-regulating market economy, scarcity, individual choice, economic development in India, trust in India's corporate sector, new institutional economics, and distribution of private property rights.
Keywords: Great Transformation, The (Book); India; NUGENT, Jeffrey; economic development; institutional economics; personal property; philosophers; scarcity; social interaction

Distributional Consequences of Globalization: Economic and Political Redistribution - Aktürk, Sener (Küresellesmenin Dagilimsal Sonuçlari ve Yeniden Siyasî Dagilim., 2003)
Bu makalede kresellesmenin ekonomik ve siyasi alanda sebep oldugu yeniden blsm (redistribution) incelenmektedir. Yazarin iddiasina gre, kresellesmeyie birlikte ekonomik alanda imalat sanayiinin, basta nc dnya lkeleri olmak zere, kresel dzlemdeki cografi yayilisina mukabil finans sektrnn merkezilesmesinde grlen yeni bir esit sosyo-ekonomik hiyerarsi ortaya ikmistir. Ekonomik alandaki bu yeniden yapilanmanin ve ortaya ikan bu "yeni hiyerarsi" nin sonucu olarak, siyasi alanda da kresellesmenin etkisi konuda ok nemli degisiklikleri gndeme getirmistir: Birincisi, devletlerin kendi i politikalari seviyesinde liberal bireycilige karsit sosyal ve cemaati akimlar glenmis, kresel liberalizm toplumsal bir karsi hareketin tepkisiyle yumusamak ve geri ekilmek zorunda kalmistir. Kresellesmenin bu makalede incelenen siyasi sonularindan diger ikisi, strasiyla, ulus-devletlerin kresellesme karsisinda ayakta kalabilmek iin blgesel organizasyonlar etrafinda bir aray gelerek glerini birlestirmeleri; dahasi, kresel hegemonyanin ve ekonomik liderligin ABD'den, basta Japonya ve in olmak zere Dogu Asya'ya geiyor olusudur. Yazar bu konudaki grslerini, kresellesmenin ekonomik boyutunu irdelerken Saskia Sassen, Manuel Castles ve Ronald Rogowski'den, siyasi boyutunu incelerken Karl Polanyi, Richard Falk, James Mittelman ve Giovanni Arrighi'nin alismalarindan yararlanarak destekliyor. (Turkish)
Keywords: computer industry; economic activity; financial services industry; foreign investments; globalization; international trade; neoliberalism; technological innovations

Idiosyncrasy and integration: suggestions from comparative political economy - Jones, Erik (Journal of European Public Policy, 2003)
There is a growing consensus in comparative political economy that 'globalization' is not eliminating the distinctive character of specific nation-states. Even in Europe, where formal integration between countries is most profound, nation-states remain idiosyncratic. Starting from this consensus, the questions I ask are: (a) how can we explain the coincidence of national idiosyncrasy and international integration; (b) what does our explanation tell us about processes of European integration? The answers, I argue, lie in two theoretical traditions -- one stemming from Karl Polanyi's (1957) insistence on the social embeddedness of market institutions and the other from Gunnar Myrdal's (1956) interpretation of the cumulative causality behind integration at the national and international levels. Although well received in other areas, neither tradition has played much of a role in the study of the European Union. The article concludes by suggesting a research program that could develop from the interface between idiosyncrasy and integration.
Keywords: MYRDAL, Gunnar, 1898-1987; convergence (economics); embeddedness; globalization; international political economy

Democracy and the Global System: A Contribution to the Critique of Liberal Internationalism - Biancardi, F. (Palgrave Macmillan UK, 2003)
Jacket abstract: "Democracy and the Global System analyses the relationship between liberal democracy and the global system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts, including Barrington Moore Jr., Karl Polanyi, Joseph Schumpeter, Samuel Huntington and David Held. While sympathetic to the aim of spreading liberal democracy globally, he demonstrates the many tensions and contradictions involved in achieving this outcome." Google books: What are the prospects of the liberal democratic form of state spreading throughout the world? Democracy and the Global System analyses the relationship between liberal democracy and the international system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts. While sympathetic to the aim of spreading liberal democracy, he demonstrates the many tensions and contradictions involved in achieving this outcome.
Keywords: democracy; international relations; political ideologies; political science